Effectiveness of Glucocorticoids in Acute Respiratory Distress Syndrome: An Umbrella Review - Semagn Mekonnen Abate; Hailemariam Mulugeta Kassim; Bivash Basu; Solomon Nega (Critical Care Research and Practice)
Objectives. Acute respiratory distress syndrome is a very challenging condition that is associated with high morbidity and mortality. This review was intended to evaluate evidence on the effectiveness of glucocorticoid treatment for acute respiratory distress syndrome. Method. A comprehensive search strategy was conducted on PubMed/Medline, Cochrane Library, Science Direct, and LILACS. Data extraction was carried out by two independent reviewers using a customized checklist. The quality of each systematic review was assessed by two independent reviewers using an AMSTAR tool, and the overall quality of evidence was generated with online GRADEpro GDT software for primary and secondary outcomes. Results. The umbrella review included nine systematic reviews and meta-analysis and one narrative review with 8491 participants. The methodological quality of the included studies was moderate-to-high quality. The overall quality of evidence and recommendations varied form high to very low. Conclusion. There is high-to-moderate quality evidence that early low-dose prolonged glucocorticoid therapy reduces mortality in ARDS. However, randomized controlled trials with large sample sizes to address ventilator-free days, the incidence of infection, and other glucocorticoid-associated adverse events are required as the quality of evidence for these secondary outcomes which were low to very low. Registration. This umbrella review was registered in PROSPERO, the International Prospective Register of Systematic Reviews (CRD42019130539).